2016
DOI: 10.1016/j.humov.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Children with developmental coordination disorder (DCD) can adapt to perceptible and subliminal rhythm changes but are more variable

Abstract: Children with DCD demonstrate impairments in bimanual finger tapping during self-paced tapping and tapping in synchrony to different frequencies. In this study, we investigated the ability of children with DCD to adapt motorically to perceptible or subliminal changes of the auditory stimuli without a change in frequency, and compared their performance to typically developing controls (TDC). Nineteen children with DCD between ages 6-11years (mean age±SD=114±21months) and 17 TDC (mean age±SD=113±21months) partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 77 publications
4
32
0
Order By: Relevance
“…A few other studies report higher variance in bimanual tapping performance among children with DCD than TD children . Although one study reported that auditory perceptual sensitivity for beat‐based timing was not significantly different between TD and DCD groups, their adaptive psychophysical measurement of perceptual sensitivity was problematic, so this null finding should be treated with caution. Finally, one study reported that children with ADHD and DCD have deficits in tapping along to the beat of music, and in extracting the beat from complex temporal structures (i.e., music) …”
Section: Are There Auditory Perceptual Timing Deficits In Dcd?mentioning
confidence: 99%
See 4 more Smart Citations
“…A few other studies report higher variance in bimanual tapping performance among children with DCD than TD children . Although one study reported that auditory perceptual sensitivity for beat‐based timing was not significantly different between TD and DCD groups, their adaptive psychophysical measurement of perceptual sensitivity was problematic, so this null finding should be treated with caution. Finally, one study reported that children with ADHD and DCD have deficits in tapping along to the beat of music, and in extracting the beat from complex temporal structures (i.e., music) …”
Section: Are There Auditory Perceptual Timing Deficits In Dcd?mentioning
confidence: 99%
“…Another reports deficits in DCD in moving various effectors to an auditory metronome . A few other studies report higher variance in bimanual tapping performance among children with DCD than TD children . Although one study reported that auditory perceptual sensitivity for beat‐based timing was not significantly different between TD and DCD groups, their adaptive psychophysical measurement of perceptual sensitivity was problematic, so this null finding should be treated with caution.…”
Section: Are There Auditory Perceptual Timing Deficits In Dcd?mentioning
confidence: 99%
See 3 more Smart Citations